2014
DOI: 10.1002/jrs.4540
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laser excitation wavelength and optical mode on Raman spectra of human fresh colon, pancreas, and prostate tissues

Abstract: Early cancer detection is the central and most important factor for allowing successful treatment and resultant positive long‐term patient outcomes. Recently, optical techniques have been applied to this purpose, although each has inherent limitations. In particular, Raman spectroscopy applied in the pathological diagnosis of cancerous tissues has received increasing attention, with the merit of being highly sensitive to the biochemical alterations in tissue compositions and applicable in vivo. Nevertheless, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The design was based on that presented by Day and Stone and is shown schematically in Figure . A 830 nm semiconductor laser (Innovative Photonics Solutions) was used to provide a superior signal/noise ratio due to lower background fluorescence than shorter wavelength excitation. , In line filters were placed approximately 15 cm from the probe tip to reduce the effect of Raman and fluorescence generated in the delivery fibers. These comprised a bandpass filter on the excitation delivery fiber and a long-pass filter on the collection fiber (Semrock Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…The design was based on that presented by Day and Stone and is shown schematically in Figure . A 830 nm semiconductor laser (Innovative Photonics Solutions) was used to provide a superior signal/noise ratio due to lower background fluorescence than shorter wavelength excitation. , In line filters were placed approximately 15 cm from the probe tip to reduce the effect of Raman and fluorescence generated in the delivery fibers. These comprised a bandpass filter on the excitation delivery fiber and a long-pass filter on the collection fiber (Semrock Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…The influence of excitation laser wavelength on the Raman signal it is well known in the scientific community and documented. [43][44][45] In reality the spectra are influenced not only by the laser wavelengths used, but also the transmission profile of the intermediary optics and diffraction grating, as well as the quantum efficiency of the CCD detector. The spectral region for Raman detection ranges from 834 nm to 960 nm depending on the laser wavelength and the Raman bands are located on the descending slope of the quantum efficiency curve of the CCD detector.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of source wavelength, 785 nm spectra had a lower background intensity than that at 830 nm, and it was found that the SNR was 1.2-1.6 times higher for 785 nm MM than that recorded from the 830 nm MM. 23 Therefore, taking this into consideration, all measurements in this study are based on a SM source.…”
Section: Source Wavelengthmentioning
confidence: 99%
“…This graph is based on eqn (5), and therefore is dependent on the assumptions that were made in its derivation; a wavelength bandwidth of 150 nm is assumed. The effect of the source optical mode for Raman spectroscopic measurement of human tissues has previously been analysed by Li et al (2014), 23 whereby the inuence of singlemode (SM) and multi-mode (MM) source lasers at 785 nm and 830 nm were compared in terms of the background signal intensity generated by tissue autouorescence and the Raman signal intensity measured from human tissue samples. Overall, a reduction in background, increase in SNR and a reduction in Mie scattering was found for 785 nm SM when compared to 785 nm MM.…”
mentioning
confidence: 99%